First-Generation Organic Reaction Intermediates in Zeolite Chemistry and Catalysis - Gong, Xuan; Çağlayan, Mustafa; Ye, Yiru; Liu, Kun; Gascon, Jorge; Dutta Chowdhury, Abhishek (Chemical reviews, 2022)
Zeolite chemistry and catalysis are expected to play a decisive role in the next decade(s) to build a more decentralized renewable feedstock-dependent sustainable society owing to the increased scrutiny over carbon emissions. Therefore, the lack of fundamental and mechanistic understanding of these processes is a critical "technical bottleneck" that must be eliminated to maximize economic value and minimize waste. We have identified, considering this objective, that the chemistry related to the first-generation reaction intermediates (i.e., carbocations, radicals, carbenes, ketenes, and carbanions) in zeolite chemistry and catalysis is highly underdeveloped or undervalued compared to other catalysis streams (e.g., homogeneous catalysis). This limitation can often be attributed to the technological restrictions to detect such "short-lived and highly reactive" intermediates at the interface (gas-solid/solid-liquid); however, the recent rise of sophisticated spectroscopic/analytical techniques (including under in situ/operando conditions) and modern data analysis methods collectively compete to unravel the impact of these organic intermediates. This comprehensive review summarizes the state-of-the-art first-generation organic reaction intermediates in zeolite chemistry and catalysis and evaluates their existing challenges and future prospects, to contribute significantly to the "circular carbon economy" initiatives.Zeolite chemistry and catalysis are expected to play a decisive role in the next decade(s) to build a more decentralized renewable feedstock-dependent sustainable society owing to the increased scrutiny over carbon emissions. Therefore, the lack of fundamental and mechanistic understanding of these processes is a critical "technical bottleneck" that must be eliminated to maximize economic value and minimize waste. We have identified, considering this objective, that the chemistry related to the first-generation reaction intermediates (i.e., carbocations, radicals, carbenes, ketenes, and carbanions) in zeolite chemistry and catalysis is highly underdeveloped or undervalued compared to other catalysis streams (e.g., homogeneous catalysis). This limitation can often be attributed to the technological restrictions to detect such "short-lived and highly reactive" intermediates at the interface (gas-solid/solid-liquid); however, the recent rise of sophisticated spectroscopic/analytical techniques (including under in situ/operando conditions) and modern data analysis methods collectively compete to unravel the impact of these organic intermediates. This comprehensive review summarizes the state-of-the-art first-generation organic reaction intermediates in zeolite chemistry and catalysis and evaluates their existing challenges and future prospects, to contribute significantly to the "circular carbon economy" initiatives.